The Evaluation Study of the Determination of the Sub-District IMB Retribution Revenue in Bandung District - Simangunsong, Fernandes (JEJAK: Jurnal Ekonomi dan Kebijakan, 2015)
The aim of this study is for knowing  the realization of IMB levy achieved by all districts in Bandung regency and their potency. This study implemented qualitative and quantitative approach with triangulation technic. After analizing the data, there are some findings. First, there are only five districts that can achieve the target of 100%. They are Pasir jambu, Cicalengka, Soreang, Kutawaringin and Cimenyan. Next, the average realization of IMB levy in Bandung regency is Rp  Rp. 820.034.365,00 or 72,53% of total target. It is is still far from the target due to some factors. They are limited human resources,  low monitoring, low society’s participation in having IMB and low motivation from implementers for carrying out the policy. Further, based on high , moderat, and low approach, the potency of receiving IMB levy is good enough. If the assumption of  IMB levy is 5%, the estimation of levy target is 47.849.901.114 with high approach, Rp 41.969.646.924 with high moderate and, Rp 36.099.392.733. with low approach.